Profile of Students' Physics Problem-solving Skills and Implementation of Quizizz-based Team Games Tournament (QTGT) Method in Physics Learning - Octa Qamar Rachmawati; Binar Kurnia Prahani; Husni Mubarok (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
This research was conducted to describe the implementation of teaching and learning activities using the Quizizz-based Team Games Tournament (QTGT) method in improving the physics problem-solving skills of senior high school students. The method of this study used preliminary research with data collection techniques in the form of written tests, which data acquisition will be analyzed descriptively qualitatively. The research was conducted on 100 students of 11th science grade from one of the Islamic high school in Gresik Regency. The results of the research show that: 1) The problem-solving skills of students in the low category with a score range of 0-50 as many as 92 students divided into 11 male students and 81 female students and the medium category in the range of score 51-75 as many as 8 students divided into 2 male students and 6 female students. 2) The lowest problem-solving skills criteria are found in the indicator C - Conceptualize the strategy (outlining the steps to be used in problem-solving) with an average score of 4.31, 3) The application of the Quizizz-based Team Games Tournament (QTGT) method is expected to improve students' physics problem-solving skills. So, it can be concluded that to improve students' physics problem-solving skills, the need for innovations in the implementation of learning such as the application of learning models and cutting-edge learning media that are packaged attractively and adapted to the current era of globalization.